Deaf studies meets autistic studies. (2nd September 2017) - Friedner, Michele; Block, Pamela
Abstract: What might deaf studies and autistic studies have in common? Why, in many cases, is deafness considered to be a norm to be analyzed through linguistic and cultural frameworks, while autism is (still) seen as pathological? Utilizing ethnographic research, participation in two conferences on autism and sign language, and an analysis of deaf peoples' and autistic peoples' self-(re)presentation, we attend to sensory solidarities that might exist between deaf and autistic people, communities, and studies. We argue that an analysis of the two fields side-by-side offers important insights into new ways of conceptualizing sociality, identity, and community both in the specific cases of deafness and autism, and more broadly. Additionally, attending to deaf and autistic peoples' language and communication desires and practices opens up analytic and empirical space for considering interdependent and multimodal communicative approaches.